2022
DOI: 10.3390/molecules27113365
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Officinaloside C against Herpes Simplex Virus-1

Abstract: The iridoid compounds in traditional Chinese medicine play a prominent role in their antiviral effects. We previously reported the anti-inflammatory effect of new iridoids from the aerial parts of Morinda officinalis. Nevertheless, several open questions remain to explore the other biological functions of these new iridoid compounds. Herpes simplex virus-1 (HSV-1) is one of the most prevalent pathogens in human beings worldwide and due to limited therapies, mainly with the guanosine analog aciclovir (ACV) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Vilhelmova-Ilieva et al showed that the cell free supernatant of L. fermentum had a potent antiviral effect when it was in contact with HSV-1 for one hour ( 25 ). Elebeedy et al demonstrated a significant decrease in HSV-1 titer (1.25 log 10 TCID 50 /ml) using the L. acidophilus supernatant ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Vilhelmova-Ilieva et al showed that the cell free supernatant of L. fermentum had a potent antiviral effect when it was in contact with HSV-1 for one hour ( 25 ). Elebeedy et al demonstrated a significant decrease in HSV-1 titer (1.25 log 10 TCID 50 /ml) using the L. acidophilus supernatant ( 26 ).…”
Section: Discussionmentioning
confidence: 99%